Combination Chemotherapy of Azacitidine and Cetuximab for Therapy-Related Acute Myeloid Leukemia following Oxaliplatin for Metastatic Colorectal Cancer - Hashimoto, Akari (S. Karger AG, 2014)
Therapy-related leukemia (TRL) has been reported to occur after treatment with alkylating agents and/or topoisomerase II inhibitors. Oxaliplatin (OXP) is used as a key drug for the treatment of colorectal cancer (CRC). Cisplatin and carboplatin have been linked with TRL, but the involvement of OXP is questionable. A 74-year-old male was diagnosed with peritoneal metastasis from CRC in July 2011. The patient received nine cycles of 5-fluorouracil (5-FU), leucovorin (LV), and OXP (mFOLFOX-6 regimen) and three cycles of 5-FU and LV only, resulting in a clinical complete response. However, recurrence of CRC was detected by CT within 3 months after the last course of chemotherapy. In April 2013, laboratory tests showed pancytopenia and 15% blast cells. A bone marrow examination revealed multilineage dysplasia and 20.4% myeloblasts. Cytogenetic analysis indicated a complex karyotype that included chromosome 5 and 7 abnormalities. The patient was diagnosed with TRL and treated with a combination of azacitidine (AZA) and cetuximab (Cmab) for both cancers. AZA might be useful in TRL when a patient needs to be treated simultaneously for more than one primary cancer because of its low toxicity. Moreover, Cmab is an effective therapeutic tool in TRL patients with metastatic CRC with the wild-type K-ras gene.